Optimalisasi Kinerja MGPS Pada Sistem Pendinginan di Kapal MT. Ketaling - Nasri; Edgar Pratama; Ali Imran Ritonga (Dinamika Bahari, 2020)
Marine Growth Prevention System (MGPS) is an anti-fouling machine used to prevent excessive growth of marine biota and rust in the sea water cooling system. The purpose of this study was to determine the decline in MGPS performance factors, the impact of these factors, and the efforts made to optimize the performance of MGPS. The method used in this study is qualitative, using Fishbone and SHEL data analysis techniques. Fishbone is used to analyze possible problem factors and then analyze and categorize problem priorities using the SHEL technique. The results of the study concluded that the decline in MGPS performance was caused by inaccurate voltage regulation, the use of anodes that exceeded the age limit, sea water conditions or elements, and lack of knowledge of an engineer. This has an impact on the MGPS performance on the cooling system on the ship. To overcome these factors, operation and maintenance of MGPS machining must be based on a manual book, replace anodes that are over the age limit, and provide training to engineers about MGPS machining